Allogeneic stem cell transplantation in patients with mantle cell lymphoma: results from the MANTLE-FIRST study on behalf of Fondazione Italiana Linfomi. Issue 14 (6th December 2021) - Arcari, Annalisa; Morello, Lucia; Vallisa, Daniele; Marcheselli, Luigi; Tecchio, Cristina; Quaglia, Francesca Maria; Tisi, Maria Chiara; Zilioli, Vittorio Ruggero; Di Rocco, Alice; Perrone, Tommasina; Gini, Guido; Dogliotti, Irene; et al.
Abstract: The role of allogeneic stem cell transplantation (allo-SCT) in mantle cell lymphoma (MCL) is uncertain, even more in the era of bruton's tyrosine kinase inhibitors (BTKi) and chimeric antigen receptor T-cells. We retrospectively analyzed 55 patients who underwent allo-SCT for MCL relapsed or refractory (r/r) after rituximab and high-dose cytarabine within the MANTLE-FIRST project. With a median follow-up of 3.7 years, non-relapse mortality (NRM), progression-free survival, and overall survival were 23%, 53%, and 56%, respectively. NRM was significantly higher in the case of acute graft-versus-host disease, > 2 prior lines of therapy, age > 60 years. The outcome was similar for patients with early (≤24 months) and late progression of disease. The use of BTKi as a bridge to allo-SCT did not increase the toxicity and allowed a good control of disease. Our real-life experience confirms that allo-SCT still represents an option in MCL patients, especially if young and early-relapsed.